2021
DOI: 10.3390/ijms22147614
|View full text |Cite
|
Sign up to set email alerts
|

PLEKHA8P1 Promotes Tumor Progression and Indicates Poor Prognosis of Liver Cancer

Abstract: Hepatocellular carcinoma (HCC) records the second-lowest 5-year survival rate despite the avalanche of research into diagnosis and therapy. One of the major obstacles in treatment is chemoresistance to drugs such as 5-fluorouracil (5-FU), making identification and elucidation of chemoresistance regulators highly valuable. As the regulatory landscape grows to encompass non-coding genes such as long non-coding RNAs (lncRNAs), a relatively new class of lncRNA has emerged in the form of pseudogene-derived lncRNAs.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…For example, NSUN5P2 was found to be unfavorable for the prognosis of hepatocellular carcinoma through bioinformatic analysis 19 . PLEKHA8P1 was also implicated as an oncogene and prognosis-related gene in both colorectal and liver cancer 20 , 21 . These results are consistent with the results of our findings in CRC.…”
Section: Discussionmentioning
confidence: 99%
“…For example, NSUN5P2 was found to be unfavorable for the prognosis of hepatocellular carcinoma through bioinformatic analysis 19 . PLEKHA8P1 was also implicated as an oncogene and prognosis-related gene in both colorectal and liver cancer 20 , 21 . These results are consistent with the results of our findings in CRC.…”
Section: Discussionmentioning
confidence: 99%
“…Given that most HCC patients are diagnosed at the intermediate and advanced stages when surgical resection is not an option, immunotherapy and systemic therapies remain the optimal treatment approaches for HCC patients. However, these therapeutic options are associated with various side effects, a heavy financial burden and worse prognostic outcomes 27 . Therefore, there is an urgent need to determine sensitive and reliable prognostic biomarkers for identifying patients with poor prognostic outcomes and those who can benefit from early adjuvant treatment, instead of salvage treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Therapeutic outcomes for HCC patients, especially early-stage liver cancer patients, largely rely on the time interval from diagnosis to the time of curative treatment initiation (TTI), thus, early diagnosis and initiation of treatment is of great importance 7 . However, most HCC patients are diagnosed in intermediate and advanced stages, thereby depriving them the best treatment opportunities, resulting in poor prognostic outcomes 8 , 9 . Therefore, there is a need to identify effective prognostic markers, with the overarching goal of improving clinical outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Relevant research has reported that PTGS2-driven inflammatory responses can induce tumor expression of microRNA-21, which can increase the level of the inflammatory mediator prostaglandin E2 (PGE2) by down-regulating PGE2-metabolizing enzymes, contributing to colorectal cancer development [ 28 32 ]. PLEKHA8P1 expression has been associated with the development and progression of many malignancies in humans, such as CRC and renal cancer [ 33 ]; moreover, research has shown that its dysregulated expression affects 5-Fluorouracil-induced chemoresistance in the human hepatocellular carcinoma cell line FT3-7 [ 34 ]. Prior studies found ZC3H12A has links with immune homeostasis and post-transcriptional regulation which can stimulate tumor progression in lung and colon cancer [ 35 37 ].…”
Section: Discussionmentioning
confidence: 99%